Projekt "Sieć wsparcia procesu inkluzji dzieci i młodzieży z niepełnosprawnością słuchu w Gdańsku" jako alternatywa rozwiązań dla Specjalistycznego Centrum Wspierania Edukacji Włączającej = The project "Support network for the inclusion of children and young people with hearing impairments in Gdańsk" as an alternative solution to the Specialised Centre for Supporting Inclusive Education - Gołubiew-Konieczna, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A very large group of students with various types of disabilities attend mainstream schools and institutions, but they need support in their education. This also applies to students with hearing impairments. In her article, the author presents children and young people with hearing impairments as a very diverse group. She also presents possible accommodations/facilities for their education resulting from education law provisions and those that are within the remit of their teachers and school specialists. She presents a project implemented in Gdańsk to support the inclusive education of children and young people with hearing impairments in the context of the implementation of Specialised Centres for Supporting Inclusive Education in the Polish education system.
Keywords: dzieci i młodzież z niepełnosprawnością słuchu; edukacja włączająca; Specjalistyczne Centrum Wspierania Edukacji Włączającej (SCWEW); children and young people with hearing impairments; inclusive education; Specialist Centre for Supporting Inclusive Education